Identification of resistant sources for gall fly, Asphondylia sesami Felt (Diptera: Cecidomyiidae) in sesame: IDENTIFICATION OF RESISTANT SOURCES FOR GALL FLY, ASPHONDYLIA SESAMI FELT IN SESAME - T BOOPATHI; K T RAMYA; A L RATHNAKUMAR (Journal of Oilseeds Research, 2022)
The incidence of the gall fly, Asphondylia sesami Felt (Diptera: Cecidomyiidae) is common during flowering period ofsesame during two seasons. The sesame genotypes (n=60) were screened for A. sesami during two season1 and 2. In season 1, two genotypes, ISWG-20-05 and IIOS-1103 were found free from A. sesami incidence. The sesame genotypes (n=60) graded for A. sesami as resistant (59 genotypes), moderately resistant (1 genotype) based on incidence. In season 2, two genotypes, SES-K-20-2015 and IC-16239 were found free from A. sesami incidence. The sesame genotypes (n=60) graded for A. sesami as resistant (29 genotypes), moderately resistant (22 genotypes), moderately susceptible (8 genotypes) and susceptible (1 genotype) based on incidence. To summarize, 28 genotypes were resistant to A. sesami in both season 1 (2021) and 2 (2022) and the resistant genotypes can be used as donor in future breeding programmes.